HBZ and its roles in HTLV-1 oncogenesis - Zhao, Tiejun; Matsuoka, Masao (Frontiers in Microbiology, 2012)
Human T-cell leukemia virus type 1 (HTLV-1) causes adult T-cell leukemia (ATL). The minus strand of HTLV-1 provirus encodes a bZIP protein donated as HTLV-1 bZIP factor (HBZ). Among the HTLV-1 regulatory and accessory genes, the tax and HBZ genes were thought to play critical roles in oncogenesis. However, HBZ is the only gene that remains intact and is consistently expressed in all ATL cases, while the tax gene is frequently inactivated by epigenetic modifications or deletion of the 5’LTR. HBZ gene promotes the proliferation of ATL cells through its mRNA form. Moreover, HBZ induces T-cell lymphoma and systemic inflammation in vivo. HBZ fulfills its functions mainly through regulating HTLV-1 5’LTR transcription and modulating a variety of cellular signaling pathways which are related with cell growth, immune response and T-cell differentiation. Taken together, the multiple functions of HBZ render its predominant function in leukemogenesis of ATL.